2020
DOI: 10.1002/jcp.29578
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‐mediated transfer of miR‐1260b promotes cell invasion through Wnt/β–catenin signaling pathway in lung adenocarcinoma

Abstract: Increasing evidence confirms that exosome-mediated transfer of microRNAs can influence cancer progression including tumor cell invasion, cell proliferation, and drug resistance via cell-cell communication. However, the potential role of exosomal-miR-1260b in lung adenocarcinoma (LAC) remains poorly understood.Thus, this study focused on investigating the function of exosomal-miR-1260b on cell invasion. Exosomal-miR-1260b was found to be higher in plasma of patients with LAC than that of healthy persons via qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…In a previous study, miR-301a was found to induce EMT in prostate cancer cells through inhibition of p63, which caused the release of ZEB1/2 in a miRNA-mediated inhibition and induction EMT [40]. Exosomal miR-1260b reportedly activates the Wnt/β-catenin signaling pathway in lung adenocarcinoma cells [41]. miR-1260b was suggested to directly suppress suppressor of cytokine singling 6 (SOCS6) expression and activate KIT proto-oncogene (KIT) signaling in non-small-cell lung cancer (NSCLC) [42].…”
Section: β-Catenin Signaling Pathwaymentioning
confidence: 89%
“…In a previous study, miR-301a was found to induce EMT in prostate cancer cells through inhibition of p63, which caused the release of ZEB1/2 in a miRNA-mediated inhibition and induction EMT [40]. Exosomal miR-1260b reportedly activates the Wnt/β-catenin signaling pathway in lung adenocarcinoma cells [41]. miR-1260b was suggested to directly suppress suppressor of cytokine singling 6 (SOCS6) expression and activate KIT proto-oncogene (KIT) signaling in non-small-cell lung cancer (NSCLC) [42].…”
Section: β-Catenin Signaling Pathwaymentioning
confidence: 89%
“…Recently, several studies have reported the predictive potential of EV-miRNAs from plasma/serum for early detection in different cancers ( 19 21 ). For instance, EV-miR-1260b in plasma was upregulated in lung adenocarcinoma and promoted cancer cell invasion by regulating Wnt/β-catenin signaling pathway ( 22 ). Low EV-miR-548c-5p in serum was associated with poor prognosis in CRC ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al [ 75 ] have demonstrated the uptake of EVs and the delivery of functional miRNAs in different cell lines. The exosomal-miR-1260b was found to be crucial for the activation of the Wnt/β-catenin signalling and the invasivness of lung adenocarcinoma cells.…”
Section: Extracellular Vesicles and The Wnt Pathwaymentioning
confidence: 99%